Finding the role of tubulin cofactor B in Toxoplasma gondii - FERNANDES, Ana Rita Martins (2024)
gondii, the causative agent of toxoplasmosis in humans and animals, is the uttermost member of apicomplexan parasites due to its zoonotic character. The accurate understanding of the proteins and mechanisms involved in T. gondii host cell invasion is crucial to develop effective vaccination strategies and new therapeutics towards the T. gondii and the Apicomplexa parasites. T. gondii tubulin cofactor B (TgTBCB) is a key protein in the host cell invasion process. TgTBCB presents a polarized localization at the apical pole, under the conoid and in close association with the polar ring and subpellicular microtubules, not co-localizing with the rhoptries and micronemes secretory vesicles present in this cellular region. TgTBCB overexpression causes a significant decrease in the capacity to invade. These data suggest that TgTBCB may be involved in the intracellular trafficking of secretory vesicles dependent on microtubules. Additionally, a preliminary screening of the TgTBCB interactome identified proteins involved in secretion, vesicular trafficking, and kinases as probable TgTBCB partners. This work aimed to characterize a T. gondii strain expressing TgTBCB without the last three amino acids residues, TBCBΔ3, to characterize TgTBCB under derepressed conditions, obtaining also a more efficient TgTBCB interactome assay and a wider vision to the mechanisms in which TgTBCB is involved. We also aimed to investigate if TgTBCB exhibits similar effects in mammalian cells as the Homo sapiens Tubulin Cofactor B (HsTBCB), using the HeLa cell line as a model. Through molecular cloning, cell culture and transfection techniques, we constructed and analyzed the expression of several TgTBCB recombinant proteins in T. gondii. While we encountered challenges in verifying the constructs, our findings provide a foundation for future research. The protein interactome of TgTBCB, once fully understood, could offer valuable insights into the parasite's invasion strategy.